Education as overcoming the Fragmentation of Life - Brito, Renato de Oliveira; Chesini, Cláudia; Lucena, José Ivaldo Araújo de; Silva, Michel Araújo; Rocha, Guilherme Felipe Santos (Technical and Scientific Journal Green Cities, 2025)
This article aims to analyze the relationship between some of the goals of SDG 4: Quality Education, with data referring to the 2023 School Census and the 2014-2024 National Education Plan, with a focus on sustainability as an element for overcoming the current fragmentation in society. The research was developed using a qualitative approach, based on bibliographic and documentary sources, such as official data from the 2023 School Census, SDG targets relating to education and the National Education Plan. Content analysis was applied to produce the results achieved. The study is original and relevant for academia and society, given that sustainability is an increasingly urgent and emerging topic for the maintenance of life and the Planet in the environmental, economic and social dimensions. As results, it was possible to perceive with this study that the theme of sustainability, although very well structured as goals of the Sustainable Development Goal - SDG 4 (quality of education), has not yet materialized as it should within the scope of Brazilian Basic Education, as it makes up the evaluation indicators of the 2023 School Census. This research is not intended to be conclusive, but it aims to contribute to the implementation of education for sustainability that is not just theoretical content, but a practice integrated into everyday school life.